Mood Disorders among Older Adults Participating in Individual and Group Active Environments: “Me” versus “Us,” or Both? - Rachael C. Stone; Brad A. Meisner; Joseph Baker (Journal of Aging Research)
Involvement in physical activity is associated with improved mental health including better social skills, coping mechanisms, and lower rates of depression. However, evidence on whether group or individual active environments better facilitate these benefits remains inconsistent. This cross-sectional cohort study examined the mental health reports of older adults (aged 50+) in relation to participation in group or individual active environments. Logistic multivariate regression analyses were conducted on the Canadian Community Health Survey (cycle 4.1, 2007-2008, n=44,057). Results illustrated that those active in both group and individual environments were 59% less likely to have a mood disorder than those who were not participating in either (P<0.001). Also, those active in both environments were 31% less likely to have a mood disorder than those active in an individual environment (P<0.001). Participating in only group or only individual environments had a similar effect compared to individuals not active in any environments for reducing rates of reported mood disorders (22% and 28%, resp.). However, the findings related to only group environments were not significant. These findings reveal that participating in both group and individual physical activities may have important implications for maintaining older adults' mental health status.